2009
DOI: 10.1111/j.1442-2042.2009.02405.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐transplant lymphoproliferative disorder following renal transplantation: A single‐center experience over 40 years

Abstract: Objectives: To investigate post-transplant lymphoproliferative disorder (PTLD) following renal transplantation at our institution. Methods: Medical records of 631 patients who underwent renal transplantation at Osaka University Hospital between March 1965 and December 2008 were reviewed. Results: PTLD following renal transplantation was detected in 10 patients (five men, five women; mean age at transplantation, 38.5 years). Mean duration from renal transplantation to the onset of PTLD was 7.1 years (range, 5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Treatment outcome in our cohort was favorable. In fact, similar observations have been made since the introduction of the monoclonal anti‐CD20 antibody rituximab (7, 11–15). Prior to the use of rituximab, reduction of immunosuppression alone resulted in a poor response rate of only 10–30% (16).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Treatment outcome in our cohort was favorable. In fact, similar observations have been made since the introduction of the monoclonal anti‐CD20 antibody rituximab (7, 11–15). Prior to the use of rituximab, reduction of immunosuppression alone resulted in a poor response rate of only 10–30% (16).…”
Section: Discussionsupporting
confidence: 53%
“…Data of PTLD from Asian populations are not well reported, and are usually restricted to case reports or series of small number of patients (6, 7). Owing to different demographics, it remains undefined if the types of PTLD and outcome are similar to those of Western patients.…”
mentioning
confidence: 99%
“…The existence of PTLD was first introduced in 1984 by Startzl et al [5]. The incidence of PTLD ranges from 1% to 3% in renal transplantation and 5% to 20% in lung and intestinal transplantation [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, large‐scale studies for PTLD have been performed and revealed several differences between early‐ and late‐onset PTLD, not only in risk and prognostic factors but also patient and graft outcome. However, the number of such reports has been limited in Asian institutions: to the best of our knowledge, only two retrospective studies of single‐center experience in China and Japan , have been reported.…”
Section: Discussionmentioning
confidence: 99%